Signaling networks and cell cycle control : the molecular basis of cancer and other diseases - Gutkind, J. Silvio (Humana Press, 2001)
Cancer Drug Discovery and Development, Volume 5> National Institutes of Health, Bethesda, MD. Describes current knowledge on signaling pathways and cell cycle control, as well as the efforts of several groups to design, synthesize, and evaluate the biochemical and biological activities of inhibiting molecules. Expanded-outline format. Extensive references. For researchers.
Cancer drug discovery and development
Keywords: biochemie; Biology; biologie; Signal Transduction; buněčný cyklus; obranné mechanismy; Cell Communication; Defense Mechanisms; PATPOLOGIE; signální transdukce; patologie; mezibuněčná komunikace; Cell Cycle